2016
DOI: 10.1186/s12933-016-0436-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary acid load and the risk of cardiovascular disease: nationwide surveys (KNHANES 2008–2011)

Abstract: BackgroundAcid–base imbalance has been reported to increase incidence of hypertension and diabetes. However, the association between diet-induced acid load and cardiovascular disease (CVD) risk in the general population has not been fully investigated.MethodsThis was a population-based, retrospectively registered cross-sectional study using nationally representative samples of 11,601 subjects from the Korea National Health and Nutrition Examination Survey 2008–2011. Individual CVD risk was evaluated using athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 51 publications
11
87
1
2
Order By: Relevance
“…In the study by Akter, no association between PRAL, NEAP and FBS or HbA 1 C was reported. Similar findings were also observed in several other studies . Akter et al reported that men in the highest quartiles of PRAL had 61% higher odds of developing diabetes compared with the lowest quartile; while no association was observed among women.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In the study by Akter, no association between PRAL, NEAP and FBS or HbA 1 C was reported. Similar findings were also observed in several other studies . Akter et al reported that men in the highest quartiles of PRAL had 61% higher odds of developing diabetes compared with the lowest quartile; while no association was observed among women.…”
Section: Resultssupporting
confidence: 88%
“…In the study by Akter et al evaluating the association between dietary acid load and prevalence of HTN in the Furukawa Nutrition and Health Study the odds of HTN in subjects in the highest tertile of PRAL and NEAP was 31% and 40% more than individuals in lowest tertile (PRAL; OR: 1.31; CI: 1.01‐1.70; NEAP OR: 1.40; CI: 1.08‐1.82) among 2028 working Japanese population. Several other studies also reported similar results of higher prevalence of HTN or higher SBP and DBP values in highest vs lowest PRAL or NEAP groupings . Only one study reported inverse association between HTN prevalence among NEAP quartiles and several other studies found no difference .…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations